Knowledge, Attitudes, Practices, and Factors Associated with Voluntary Blood Donation among University Students in Kilimanjaro, Tanzania. (14th December 2016) - Elias, Elionora; Mauka, Wilhellmuss; Philemon, Rune N.; Damian, Damian J.; Mahande, Michael J.; Msuya, Sia E.
Abstract : Background . Understanding the knowledge and awareness of blood donation among potential blood donors in the population, like young people, and the associated attitudes and practices is important. Methodology . This was a cross-sectional study whereby a self-administered questionnaire was used to collect information from the consenting participants. Results . A total of 422 participants were enrolled. Their mean age was 24.2 (SD 3.6) years. Of the 422, 30% have ever donated blood. 55% of those who had ever donated were repeated blood donors. Majority of the participants (93%) had positive attitudes towards blood donation and 88% were willing to donate in the future. Factors that were significantly associated with ever donating blood were male gender, knowing a person who has donated blood, knowledge of the amount of blood donated, willingness to donate in the future, and not expecting any postdonation reward. Discussion . High awareness, positive attitude, and high intention to donate in the future should be used to underscore the need to educate the young people on the value of blood donation in saving lives and to give them correct information on overall requirements for blood donation.